(untitled) (Islas, 2024)
Introduction: This study assesses the valuable contributions of Argentine philosopher Arturo Andrés Roig to the history of Latin American ideas. From the perspective of a "practical humanism", his work moves beyond traditional abstract humanism, particularly in its treatment of the concepts of freedom and social justice. Methods: Using the scientific research methodology of the history of ideas, the study analyzes Arturo Andrés Roig’s books, articles, interviews, and presentations, focusing on his reflections on freedom and social justice. Results: Arturo Andrés Roig’s practical humanism enriches the study of humanism in Latin American thought through his analysis of the human condition, freedom, and social justice, offering a critical transcendence of Eurocentrism and significant reflections on the functions of philosophy. Conclusions: The practical humanism of Arturo Andrés Roig contributes to the study of humanism in Latin American thought in his analysis of the human condition, freedom and social justice in his critical overcoming of Eurocentrism and in his reflections on the functions of philosophy.